Collaborative Governance of Government and Millennial Farmers in Creating a Sustainable Agricultural Ecosystem in the Nusantara Capital City - Sri Suparni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Abstract This study is a qualitative study with a descriptive approach that describes a number of advantages and disadvantages of collaboration between the Ministry of Agriculture and millennial farmers in creating a sustainable agricultural ecosystem. The data used in this article are secondary data that researchers obtain from a number of sources that are commonly used in every study, namely books, scientific articles, and credible websites. The data are collected, selected, described, analyzed with SWOT, and finally conclusions are drawn. The result in this article show the Collaboration between the government of the Republic of Indonesia in this case represented by the Ministry of Agriculture has more strength and advantages, among others, millennial farmers are in productive age so that agricultural productivity can increase through the ideas they have, mastered technology, and good vision. In addition, on the government side it also benefits because the Ministry of Agriculture has a program that is in line and strong power. Through this, the results can benefit both parties and even the Indonesian nation by creating a sustainable agricultural ecosystem. Keywaords: Collaborative Governance of Government, Millennial Farmers ,Sustainable Agricultural Ecosystem